A Contribution Evaluation and Reward Framework Based on Shapley Value and Smart Contract - Chen, Shengdong (Innovative Applications of AI, 2024)
Currently, the advantages of Shapley value in explaining model decisions have made incentive mechanisms Shapley value contribution assessment based become major research focus. This approach ensures the effectiveness and fairness of contribution assessment algorithms. However, there is a significant issue regarding the reliability of the computational results. Additionally, traditional Shapley value-based contribution processes face an issue where computational complexity increases exponentially with the number of participants. Addressing these issues, this paper proposes a contribution assessment and reward framework based on Shapley value and smart contract technology using alliance blockchain. This framework overcomes the reliance on third-party institutions that is characterized by traditional incentive mechanisms, leveraging the decentralized nature of blockchain to eliminate trust issues associated with a single centralized entity. Furthermore, the traceability of blockchain ensures the transparency and traceability of the contribution assessment and reward distribution processes.